Self-confidence level of users of dating applications in Tridinanti University Students - Risca Firlianty; Nuzsep Almigo (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The study aimed to examine the use of online dating apps among Tridinanti University students and its relationship with confidence levels. Based on an initial survey conducted in January 2024 with 322 respondents, it was found that students of Tridinanti University use online dating apps as a necessity in finding a partner. The majority of users have been using the app for more than a year, with an average usage of about two hours per day. The survey results show that college students who use online dating apps tend to have lower levels of self-confidence, being more comfortable dating through apps than in person. Ninety-two students were embarrassed to initiate a face-to-face encounter, 76 students lacked confidence in their physical appearance, and 29 students did not have time to seek a face-to-face partner. In addition to surveys, the study also involved observation and interviews to delve into this phenomenon. The research uses a combination method (mix method) with a quantitative and qualitative approach, adopting a sequential explanatory model. The data was collected through a Likert scale and tested for validity and reliability using SPSS version 20.0. The results of this study are expected to provide a deeper understanding of the impact of using online dating apps on student self-esteem.